The Effect of Company Size and Sustainability Reporting on Profitability with Good Corporate Governance as a Moderating Variable - Nanda Dwi Wahyu Bima Atmojo; Nandhiko Wahyu Mukti; Muhammad Akmal Baskoro; Arsyifa Maulidina; Bambang Subiyanto (Peneliti.net, 2026)
This study analyzes the effect of company size and Sustainability Reporting (SR) on Profitability (PR) with the Audit Committee (AC) as a moderating variable determined for Good Corporate Governance (GCG), in companies listed on the IDX80 Index on the IDX in 2020-2024, the research are tested using WarpPLS 8.0 as the statistical program. It was concluded that company size has a significant negative effect on profitability, while sustainability reporting and the moderating role of good corporate governance (GCG) are not significant with profitability